Meningkatkan Hasil Belajar Menggunakan PBL, Example Non Example, Dan Talking Stick - Elsa Rahmayanti; Susilawaty (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem faced which is the object of this research is that students do not participate in the learning process and find it difficult to concentrate. Problem-based learning, Example Non Example, and Talking Stick are used to solve the problem. The purpose of this study was to describe teacher activities, as well as analyze student activities and learning outcomes. This research used qualitative and quantitative approaches, namely Classroom Action Studies (PTK) which were carried out in two cycles with two meetings in each cycle in class 5 UPTD SDN 1 Banyu Irang, totaling 9 students. The level of learning success with learning completeness, for example 81% of students achieved a KKM score greater than 80. The results showed an increase at each meeting where the teacher became active in implementing the learning pola. In Cycle 1 the teacher got a maximum score of 32 out of 44, and in Cycle 2 it reached 40 out of 44. The maximum score is 'Very Good'. In cycle I student activeness was 55%, and in cycle II with the criteria "Very active" increased to 100%. In addition, the completeness of student learning outcomes increased from 77% in one cycle to 100% in two cycles with an average of 95.